2020
DOI: 10.3390/ijgi9110683
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding Spatial-Temporal Patterns of Taxi Trip based on an Improved Network Kernel Density Estimation

Abstract: Taxi mobility data plays an important role in understanding urban mobility in the context of urban traffic. Specifically, the taxi is an important part of urban transportation, and taxi trips reflect human behaviors and mobility patterns, allowing us to identify the spatial variety of such patterns. Although taxi trips are generated in the form of network flows, previous works have rarely considered network flow patterns in the analysis of taxi mobility data; Instead, most works focused on point patterns or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…As the industry matures, more methods are applied to charging infrastructure demand forecasting, such as: travel chain theory [4][5][6][7] Grey forecast model [8] , Cumulative Prospect Theory [9,10] and simulation methods based on Monte Carlo, etc. [11][12][13][14] . Historical studies have shown that each method has its own unique advantages and applicability, however, current studies mainly focus on micro scenarios, such as a small or mediumsized area within a city, and lack of macro-view forecasting and research, which makes it difficult to provide direct support for the industry's high-quality development as well as for the business planning decisions of enterprises.…”
Section: Forewordmentioning
confidence: 99%
“…As the industry matures, more methods are applied to charging infrastructure demand forecasting, such as: travel chain theory [4][5][6][7] Grey forecast model [8] , Cumulative Prospect Theory [9,10] and simulation methods based on Monte Carlo, etc. [11][12][13][14] . Historical studies have shown that each method has its own unique advantages and applicability, however, current studies mainly focus on micro scenarios, such as a small or mediumsized area within a city, and lack of macro-view forecasting and research, which makes it difficult to provide direct support for the industry's high-quality development as well as for the business planning decisions of enterprises.…”
Section: Forewordmentioning
confidence: 99%
“…Zheng et al used the taxi trajectory data to investigate the spatial layout and the allocation of management resource of the urban public green space from the spatial interaction perspective [62]. Shen et al analyzed the spatiotemporal pattern of taxi travel based on an improved network kernel density estimation method [63]. Gao et al investigated the impact of the modifiable areal unit problem (MAUP) for understanding the relationships between commuting demand and built environment [64].…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…The two NKDEs correcting the density at intersections have been widely adopted in practice (Mohaymany, Shahri, and Mirbagheri, 2013; Dai and Jaworski, 2016; Harirforoush and Bellalite, 2019; Shen et al, 2020), in part, due to its implementation in the SANET software (Okabe, Okunuki, and Shiode, 2006). The approach proposed by Xie and Yang (2008) is still used (Li et al, 2011; Lesage‐Mann and Apparicio, 2016; Rui et al, 2016) because it can easily be implemented in traditional GIS software and because of its intuitive character.…”
Section: Introductionmentioning
confidence: 99%